How do changes in market fundamentals affect hedging in US live cattle markets? - Ac Pangan, Walter Oliver (Kansas State University, 2021)
When basis variability increases, it complicates hedging price risk management and causes hedging effectiveness to decrease. This is one reason that volatility in US live cattle basis has raised concerns over the last decade. It is vital for participants in live cattle cash markets to improve their understanding of how shifts in market conditions affect basis variability. The purpose of this analysis is to evaluate how changes in market fundamentals and price momentum impact live cattle hedging effectiveness and how the impacts vary regionally across Kansas, Nebraska, and Iowa-Minnesota. Identifying and measuring these impacts provide insights to improve the basis predictability and help manage live cattle hedging risk. This study used weekly data from June 2007 to December 2019 to estimate regional hedonic models where the dependent variable was Basis Prediction Error (the difference between actual Basis and Expected Basis), which serves as a hedging effectiveness measure, and the independent variables represent the shifts in the market fundamentals. The results show that the changes in the factors such as total head marketed in all markets, the thinness of the negotiated market, weight of the live cattle marketed, the current premium for high-quality beef, and the cost of gain have statistically significant relationships with Basis Prediction Error. It is essential to highlight that the statistical significance, direct impact, and magnitude for most of the variables vary across the regions and over time. The analysis of volatility using the parameter estimates and a one standard deviation shock to respective variables showed that the changes in current premium for high-quality beef and the changes in the cost of gain have a higher monetary impact on hedging outcome basis than other variables evaluated.
Keywords: Hedging; Basis; Risk management; Live cattle; Futures contract